Meteorological data from Alesjaure - Tarfala Research Station (Stockholm University, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Tarfala Research Station (2025). Meteorological data from Alesjaure, 2014-01-01–2014-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/jBOqX-FFMMEE70wR22KAj6wI
Keywords: Tarfala Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Incoming shortwave radiation; Incoming shortwave radiation; Wind speed; Wind speed; Wind direction; Wind direction; Snow depth; Snow depth; Soil temperature; Soil temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap